Does Personality Matter? Small Business Owners and Modes of Innovation~ - Petrik Runst; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2020)
The DUI (learning by doing-using-interacting) mode offers a promising theoretical framework to explain why many small and medium-sized enterprises (SMEs) are successful in innovation without research and development (R&D) efforts. In this context, we argue that - because of the informal, person-centered, and interactive nature of the DUI mode - small business owners should be in a key position to trigger DUI learning processes at the company level. Based on a large SME data set from Germany, we show empirically that Big Five personality traits of small business owners positively affect self-selection into DUI-based innovation in less R&D-intensive SMEs. That is, companies operating largely under the DUI mode seem to benefit in particular from certain owners' personality characteristics. In addition, we present novel evidence that complementarities between different Big Five traits exist in terms of self-selection into the DUI mode, thereby pointing to the role of certain personality prototypes. The paper concludes with implications for policy and further research.
Keywords: O31; O32; D91; 330; modes of innovation; non-R&D innovation; Big Five personality traits; personality prototypes; SMEs